Edible bamboo shoots: a sustainable nexus of nutrition, livelihood, and food security for rural communities in India - Sarkar, Pradip Kumar; Bhattacharjee, Bijoya; Das, Sujit; Das, Bapi; Singh, N. Raju; Bhutia, Pempa L.; Chakrabarti, A.; Das, Bikash; Podder, Rubai; Choudhury, Burhan U. (Frontiers in Nutrition, 2025)
Bamboo, a fast-growing, durable, and versatile natural resource, plays a significant role in the livelihoods of rural communities in India by providing economic, ecological, and nutritional benefits. With its multifaceted utility, bamboo contributes to poverty alleviation, biodiversity conservation, and ecosystem restoration. While bamboo culms find extensive industrial use, edible bamboo shoots, particularly in the northeastern and eastern regions of India, have emerged as a vital food source rich in macro- and micronutrients. Species such as Bambusa balcooa, B. bambos, B. vulgaris, Dendrocalamus asper, D. hamiltonii, D. giganteus, and Melocanna baccifera are highly valued both for their edible shoots and ecological services. Despite challenges like cyanogenic toxicity, short shelf-life, and market linkages, improved processing techniques, fermentation practices, and agroforestry-based cultivation offer immense potential for sustainable agriculture, livelihood enhancement, and climate-resilient food systems. This review highlights the significance of edible bamboo shoots as a sustainable bridge between nutrition, livelihood, and food security in India, along with technological interventions and policy support needed to maximize their potential.